2016
DOI: 10.1002/smj.2504
|View full text |Cite
|
Sign up to set email alerts
|

Shareholder perceptions of the changing impact of CEOs: Market reactions to unexpected CEO deaths, 1950–2009

Abstract: Research summary: Despite a number of studies highlighting the important impact Chief Executive Officers (CEOs) have on firms, several theoretical and methodological questions cloud existing findings. This study takes an alternative approach by examining how shareholders' perceptions of CEO significance have changed over time. Using an event study methodology and a sample of 240 sudden and unexpected CEO deaths, we show that absolute (unsigned) market reactions to these events in U.S. public firms have increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…To compile our sample of sudden executive (CEOs, chairmen and presidents) deaths for the period 1980 to 2012, we use the data from Salas (2010), who identifies suddenly deceased CEOs, chairmen and presidents, and complement it with data on sudden CEO deaths from Quigley, Crossland, and Campbell (2016). The sample period in the two aforementioned studies ends in 2008 and 2009, respectively.…”
Section: Sample Selection and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…To compile our sample of sudden executive (CEOs, chairmen and presidents) deaths for the period 1980 to 2012, we use the data from Salas (2010), who identifies suddenly deceased CEOs, chairmen and presidents, and complement it with data on sudden CEO deaths from Quigley, Crossland, and Campbell (2016). The sample period in the two aforementioned studies ends in 2008 and 2009, respectively.…”
Section: Sample Selection and Datamentioning
confidence: 99%
“…In specifications 3and 4, we address time trends as another alternative explanation. Using a sample of executive sudden deaths between 1950 and 2009, Quigley, Crossland, and Campbell (2016) provide evidence that the value of executives and/or their impact on the firms they run has increased over time. Given the positive time trend of the general ability index we report in Figure 2, our evidence of a positive valuation effect of general managerial skills might just reflect the generally increasing value (and impact) of executives over time.…”
Section: Alternative Explanationsmentioning
confidence: 99%
“…We are grateful to Tim Quigley for sharing the information on unexpected CEO deaths used in Quigley et al ().…”
mentioning
confidence: 99%
“…Even owners have demonstrated a greater significance and influence for executives on firm outcomes. In a recent study to unexpected CEO deaths, Quigley, Crossland, and Campbell (2017) empirically showed that shareholders react to unexpected CEO deaths in an amplified way that clearly confirms the belief that CEOs have become very influential particularly to firms' outcomes. Therefore, there is an ample of scientific support and empirical evidence for the importance of executives and their effect on firm performance when they are accorded with greater levels of discretion.…”
Section: Comments On the Importance Of Managerial Discretion In Corpomentioning
confidence: 69%